2017
DOI: 10.3390/su9050854
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Environmental Management Indicators in South African Primary Schools

Abstract: This research explores sustainable environmental management indicators in South African primary schools. Of key interest is the comparison of a township, farm and urban primary school that identify indicators that promote education for sustainable development in schools that implement an environmental management system. Data are drawn from one-on-one interviews, focus group interviews, observations and document analysis from 35 participants in three schools. A comparison of the three schools was done by conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…The findings are contrary to Coertjens et al (2010) where it was shown that schools which implement hands-on science teaching methods and environmental learning activities are linked to higher levels of environmental awareness and more pro-environmental attitudes among students. Sousa et al (2017) and Prestoza (2024)…”
Section: Level Of Environmental Awareness On Initiated Activitiesmentioning
confidence: 99%
“…The findings are contrary to Coertjens et al (2010) where it was shown that schools which implement hands-on science teaching methods and environmental learning activities are linked to higher levels of environmental awareness and more pro-environmental attitudes among students. Sousa et al (2017) and Prestoza (2024)…”
Section: Level Of Environmental Awareness On Initiated Activitiesmentioning
confidence: 99%
“…Um espaço educador torna-se sustentável quando toda a escola passa por transformações, com aspectos que abrangem desde sua estrutura física, gestão e os impactos gerados na comunidade, produzindo conhecimentos e atitudes favoráveis à sustentabilidade ambiental (BRITO; SIREVES; CUNHA, 2019). Para tal, o auxílio de estudos que avaliam sustentabilidade em unidades educacionais faz-se necessário, envolvendo metodologias aplicadas com o uso de métodos quali-quantitativos e mistos em: estudos de caso (LIZANA et al, 2021;FEHR, 2015;SOUSA;RICHTER;RAATH, 2017;; consultas a especialistas através da aplicação de questionários (HO; CHEN; HSU, 2017; SARAIVA et al 2019); proposições de indicadores (SARAIVA; ALMEIDA; BRAGANÇA, 2018); ou documentos (HOLST et al, 2020). Dentre as ferramentas de gestão com potencial para avaliar a sustentabilidade em unidades escolares estão: A3P, Eco Schools, Selo Escola Sustentável e Resiliente, Escola Sustentável, GRI e LEED Schools, apresentadas a seguir.…”
Section: Revisão Bibliográficaunclassified
“…As the development of environmental education occurs mainly through recreational activities that show great educational potential for contributing in the process of human development (Maciel et al, 2022). This is a strong indicator that these studies are embedded in a system of environmental education in order to achieve the global Sustainable Development Goal for excellent education (De Sousa et al, 2017). Which prompt the researcher to find out the instructional methodologies used by teachers to integrate environmental education.…”
Section: Empirical Reviewmentioning
confidence: 99%